Dynamic Inefficiencies in an Employment-Based Health Insurance System: Theory and Evidence - Fang, Hanming; Gavazza, Alessandro (American Economic Review, 2011)
We investigate the effects of the institutional settings of the US health care system on individuals' life-cycle medical expenditures. Health is a form of general human capital; labor turnover and labor-market frictions prevent an employer-employee pair from capturing the entire surplus from investment in an employee’s health. Thus, the pair underinvests in health during working years, thereby increasing medical expenditures during retirement. We provide empirical evidence consistent with the comparative statics predictions of our model using the Medical Expenditure Panel Survey (MEPS) and the Health and Retirement Study (HRS). Our estimates suggest significant inefficiencies in health investment in the United States.